The Portrayal of Men and Women in Arabic Textbooks: Insight from Indonesian Pesantren - Batmang Batmang; Khofifah Khofifah; Abdul Gaffar; Fahmi Gunawan (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
Although gender representation in Arabic textbooks has been extensively documented, little is known about it from the perspective of local textbooks. To fill this void, the present study aims to examine gender representation in Arabic textbooks at one of the most prominent Islamic Boarding Schools in Kendari, Southeast Sulawesi, Indonesia. This study uses a case study research design and Choiroh and Taufiq's theory (2020) to analyze data. The research findings revealed that the gender representation in that textbook encompasses stereotypes, subordination, marginalization, and double burden in the themes of time, sports professions, and patient clinics. The factors behind the emergence of gender representation were classified into internal and external factors. Internal factor is caused by being written by a female Arabic teacher, while external factor includes patriarchal culture. This research implies that teachers or instructors in Islamic boarding schools need training or workshops to discuss gender equality so that stereotyping, marginalization, and the double burden that disadvantages women can be considered and avoided.